The Implementation of the Independent Curriculum through Independent Project on Sustainable Lifestyle Theme for Grade 10 Students - Mila Ermila Hendriyani; Veny Rafenia; Selfi Maharani; Hidayatullah Al-Azis (Jurnal Pendidikan Indonesia Gemilang, 2023)
This study aimed to determine the implementation of the Independent Curriculum project with the theme of a sustainable lifestyle in class X at one of the senior high schools in Pandeglang, Indonesia. The method used in this research is descriptive research through a qualitative approach with data collection techniques, namely questionnaires of 140 sample class X students at one of the senior high schools in Pandeglang, Indonesia. The independent curriculum is an intracurricular learning curriculum that gives students more time to explore concepts and competencies. One of the programs from the Independent Curriculum is Pancasila Student Profile Strengthening Project, or the Pancasila Student Profile Strengthening Project, with the theme of a sustainable lifestyle. Pancasila Student Profile Strengthening Project activities in this independent curriculum have a positive impact. Based on the research results, 70.7% of class X students agreed that implementing Pancasila Student Profile Strengthening Project with the theme of a sustainable lifestyle had an impact and was effective for students in caring for the environment.